The Ethical Challenges Faced by Nurses Providing Care to Patients with COVID-19: A Qualitative Content Analysis - Fereshteh Ghaljaei; Majid Reza Akbarizadeh; Mahin Naderifar (Journal of Qualitative Research in Health Sciences)
Background: Nurses most frequently face ethical challenges due to their direct contact with patients. Accordingly, the present study aimed to investigate the ethical challenges faced by nurses who provided care to patients with COVID-19.Methods: This qualitative study was conducted using conventional content analysis. A total of 13 nurses who were selected through purposive sampling participated in the study. Data were collected via in-depth and semi-structured interviews until data saturation from June to late November 2021. Data were analyzed simultaneously with data collection using qualitative content analysis based on the steps proposed by Graneheim and Lundman. Besides, data accuracy and robustness were checked, and ethical standards were followed.Results: Data analysis led to the identification of two main themes including threatening adherence to professional obligations and experiencing moral distress in patient care.Conclusion: Based on the findings, nurses mentioned a large number of ethical challenges such as the risk of injustice and loss of responsibility in providing care, decision conflicts, weakening ethical concepts such as patience and kindness, conflict between professional obligations and personal commitments, and the lack of attention to metaphysical beliefs. The results of this study highlighted the importance of educational planning, psychological and economic support, gratitude and empathy shown by authorities, providing security in the workplace, and developing face-to-face psychological interventions based on nursing needs.